Phase-specific and lifetime costs of cancer care in Ontario, Canada. Issue 1 (December 2016) - de Oliveira, Claire; Pataky, Reka; Bremner, Karen; Rangrej, Jagadish; Chan, Kelvin; Cheung, Winson; Hoch, Jeffrey; Peacock, Stuart; Krahn, Murray
Abstract Background Cancer is a major public health issue and represents a significant economic burden to health care systems worldwide. The objective of this analysis was to estimate phase-specific, 5-year and lifetime net costs for the 21 most prevalent cancer sites, and remaining tumour sites combined, in Ontario, Canada. Methods We selected all adult patients diagnosed with a primary cancer between 1997 and 2007, with valid ICD-O site and histology codes, and who survived 30 days or more after diagnosis, from the Ontario Cancer Registry (N = 394, 092). Patients were linked to treatment data from Cancer Care Ontario and administrative health care databases at the Institute for Clinical and Evaluative Sciences. Net costs (i.e., cost difference between patients and matched non-cancer control subjects) were estimated by phase of care and sex, and used to estimate 5-year and lifetime costs. Results Mean net costs of care (2009 CAD) were highest in the initial (6 months post-diagnosis) and terminal (12 months pre-death) phases, and lowest in the (3 months) pre-diagnosis and continuing phases of care. Phase-specific net costs were generally lowest for melanoma and highest for brain cancer. Mean 5-year net costs varied from less than 25, 000 for melanoma, thyroid and testicular cancers to more than 60, 000 for multiple myeloma and leukemia. Lifetime costs ranged from less than 55, 000 for lung and liver cancers to over 110, 000 for leukemia, multiple myeloma, lymphoma and breast cancer. Conclusions Costs of cancer care are substantial and vary by cancer site, phase of care and time horizon analyzed. These cost estimates are valuable to decision makers to understand the economic burden of cancer care and may be useful inputs to researchers undertaking cancer-related economic evaluations.